Brugada Syndrome in Women: What Do We Know After 30 Years? - Martínez-Barrios, Estefanía; Arbelo, Elena; Cesar, Sergi; Cruzalegui, José; Fiol, Victoria; Díez-Escuté, Nuria; Hernández, Clara; Brugada, Ramon; Brugada, Josep; Campuzano, Oscar; Sarquella-Brugada, Georgia (Frontiers in Cardiovascular Medicine, 2022)
Brugada syndrome (BrS) was initially described in 1992 by Josep and Pedro Brugada as an arrhythmogenic disease characterized by ST segment elevation in the right precordial leads and increased risk of sudden cardiac death (SCD). Alterations in the SCN5A gene are responsible for approximately 30% of cases of BrS, following an autosomal dominant pattern of inheritance. However, despite its autosomal transmission, sex-related differences are widely accepted. BrS is more prevalent in males than in females (8–10 times), with males having a 5.5-fold higher risk of SCD. There are also differences in clinical presentation, with females being more frequently asymptomatic and older than males at the time of diagnosis. Some factors have been identified that could explain these differences, among which testosterone seems to play an important role. However, only 30% of the available publications on the syndrome include sex-related information. Therefore, current findings on BrS are based on studies conducted mainly in male population, despite the wide acceptance of gender differences. The inclusion of complete clinical and demographic information in future publications would allow a better understanding of the phenotypic variability of BrS in different age and sex groups helping to improve the diagnosis, management and risk management of SCD.